A retrospective database analysis to estimate the burden of AOM in children <15y in Veneto region. (30th September 2020) - Barbieri, E; Cantarutti, A; Porcu, G; Hu, T; Petigara, T; Prandi, G M; Alimenti, C; Scamarcia, A; Cantarutti, L; Giaquinto, C
Abstract: Background: Acute Otitis Media (AOM) causes substantial healthcare resource utilization (HCRU) in children. This analysis assessed AOM HCRU and costs following PCV13 introduction in 2010 in Veneto. Methods: AOM episodes in children <15 years residing in Veneto were identified in Pedianet, a pediatric primary care, database from 2010-2017. Recurrent AOM was defined as at least three episodes in 6 months, or four or more episodes in 12 months. HCRU includes primary care visits, antibiotic prescriptions, diagnostic tests, specialist visits, emergency room (ER) visits and hospitalizations. Incidence rates (IRs) were numbers of episodes/1, 000 person-years. Standardized regional incidence rates (SRIRs) were calculated by standardizing IRs with regional population data by age and year. Regional expenditures (€/1, 000 person-years) were calculated by multiplying SRIRs with average cost per episode. Results: Simple AOM episodes were associated with 1.03 primary care visits and 1.52 antibiotic prescriptions on average. Only 2.4% and 0.18% of simple AOM episodes included an ER visit, and a hospitalization respectively. Recurrent AOM episodes were associated with 1.06 primary care visits and 1.62 antibiotic prescriptions. Annual costs per episode were €50 for simple AOM and €54.2 for recurrent AOM, majority of which were associated with primary care visits and antibiotic prescriptions. Average antibiotic prescription costs were €14.2 for simple AOM and €16 for recurrent AOM. During 2010 and 2017, SRIRs declined from 100 to 72/1000 person-year for simple AOM and from 13 to 11/1, 000 person-year for recurrent AOM. Regional expenditures decreased from €4702.7 to €3358.5/1, 000 person-year for simple AOM and from €672.4 to €572.6/1000 person-year for recurrent AOM. Conclusions: SRIRs and regional expenditures declined for simple and recurrent AOM after PCV13 introduction. Primary care visits and antibiotic prescriptions account for the majority of expenditures. Key messages: SRIRs and regional expenditures declined for simple and recurrent AOM after PCV13 introduction. Primary care visits and antibiotic prescriptions account for the majority of expenditures.